Optimal fiscal management of commodity price shocks - Agenor, Pierre-Richard (Journal of development economics, 2016)
This paper analyzes how low-income countries should optimally respond, through fiscal policy, to commodity price shocks. The model accounts for imperfect access to world capital markets and a variety of externalities associated with public infrastructure, including utility benefits, a direct complementarity effect with private investment, and reduced distribution costs. However, public capital is also subject to congestion and absorption constraints, with the latter affecting the efficiency of infrastructure investment. The optimal windfall allocation rule between spending today and asset accumulation is determined so as to minimize a social loss function defined in terms of the volatility of private consumption and either the nonresource primary fiscal balance or a more general index of macroeconomic stability, which accounts for the volatility of the real exchange rate.